Maintenance management of public building managed by municipal council of Penang Island / Noor Salwani Shaari - Shaari, Noor Salwani (Faculty of Architecture, Planning and Surveying, 2009)
Maintenance Management is a combination of several actions in which to retain or restore an item to perform its required action. Improper supervision has lead to poor performance which was due to lack of public building objective. Therefore, based on this research the maintenance management by municipal council to the public building should be considered. This study focused on identifying the factors of implementing maintenance management of public building, identifying the perception of occupants toward the maintenance management which implemented by Municipal Council of Penang Island (MPPP) and to improve the maintenance management for public building by MPPP. In order to achieve the objectives identified, literature review was done, and then the data was collected using questionnaires. The output of research from the data analysis is achieved by Microsoft Excel 2003. Finding shown that even though that the food court building has the maintenance unit to monitor and control that building, the occupants of the building still in average level toward the maintenance at the food court building. Hence, the local authority should be to improve the maintenance management toward the food court building with increasing the quality of work.